2021
DOI: 10.1016/j.dib.2020.106664
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and photocatalytic scavenging of 2-chlorophenol using carbon nitride-titania nanotubes based nanocomposite: Experimental data, kinetics and mechanism

Abstract: Adsorption and interaction of pollutant species on surface of the catalyst materials play an important role on the photocatalysis process. Herein, experimental data on the adsorption behavior of 2-chlorophenol (2-CP) onto graphitic pure carbon nitride (C 3 N 4 ), titania nanotubes (TiO 2 —NTs) and carbon nitride/titania nanotubes nanocomposite (C 3 N 4 /TiO 2 —NTs) from synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…One of the developments in dye treatment is via the combination of adsorption-photodegradation processes [ 4 , 5 ]. Several studies reported using SBA-15 and silica combined with carbon nitride or titania as an efficient photocatalyst for dye removal [ 4 , 6 , 7 , 8 , 9 ]. The method offers simultaneous adsorption of pollutants followed by photodegradation under light irradiation to decompose the adsorbed pollutants into less harmful molecules [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the developments in dye treatment is via the combination of adsorption-photodegradation processes [ 4 , 5 ]. Several studies reported using SBA-15 and silica combined with carbon nitride or titania as an efficient photocatalyst for dye removal [ 4 , 6 , 7 , 8 , 9 ]. The method offers simultaneous adsorption of pollutants followed by photodegradation under light irradiation to decompose the adsorbed pollutants into less harmful molecules [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given its resistance to degradation, 2-CP tends to accumulate in natural settings. Because of its potency as a mutagen and carcinogen, 2-CP is disastrous for aquatic ecosystems (Barakat et al, 2021). This means that before discharge, 2-CP must be removed from industrial effluent.…”
Section: Introductionmentioning
confidence: 99%
“…However, ACF/photocatalyst composite materials are little studied in the field of wastewater treatment [38]. In this category, different types of fibers can be found, such as commercial fabrics [12,39,40], fibers made from natural resources such as coconut [41], carbon nanotubes [42,43], and graphene-like materials [44]. For commercial activated carbon fibers, studies are often focused on the materials (i.e., on the synthesis or deposition of the coating and its characterization).…”
Section: Introductionmentioning
confidence: 99%